SARS-CoV-2 N Protein Induces Acute Lung Injury in Mice via NF-ĸB Activation - Xia, Jie; Tang, Wenqi; Wang, Jiangmei; Lai, Dengming; Xu, Qi; Huang, Ruoqiong; Hu, Yaoqin; Gong, Xiaojue; Fan, Jiajie; Shu, Qiang; Xu, Jianguo (Frontiers in Immunology, 2021)
Background: Infection of SARS-CoV-2 may cause acute respiratory syndrome. It has been reported that SARS-CoV-2 nucleocapsid protein (N-protein) presents early in body fluids during infection. The direct involvement of N-protein in lung injury is poorly understood. Methods: Recombinant N-protein was pretreated with polymyxin B, a lipopolysaccharide (LPS)-neutralizing agent. C57BL/6, C3H/HeJ (resistant to LPS), and C3H/HeN (control for C3H/HeJ) mice were exposed to N-protein via intratracheal administration to examine acute lung injury. In vitro, bone marrow–derived macrophages (BMDMs) were cultured with N-protein to study phosphorylation of nuclear factor kappa B (NF-ĸB) p65, macrophage polarization, and expression of proinflammatory cytokines. Results: N-protein produced acute lung injury in C57BL/6 mice, with elevated protein permeability, total cell count, neutrophil infiltration, and proinflammatory cytokines in the bronchioalveolar lavage. N-protein also induced lung injury in both C3H/HeJ and C3H/HeN mice, indicating that the effect could not be attributed to the LPS contamination. N-protein triggered phosphorylation of NF-ĸB p65 in vitro, which was abolished by both N-protein denaturation and treatment with an antibody for N-protein, demonstrating that the effect is N-protein specific. In addition, N-protein promoted M1 macrophage polarization and the expression of proinflammatory cytokines, which was also blocked by N-protein denaturation and antibody for N-protein. Furthermore, N-protein induced NF-ĸB p65 phosphorylation in the lung, while pyrrolidine dithiocarbamate, an NF-ĸB inhibitor, alleviated the effect of N-protein on acute lung injury. Conclusions: SARS-CoV-2 N-protein itself is toxic and induces acute lung injury in mice. Both N-protein and NF-ĸB pathway may be therapeutic targets for treating multi-organ injuries in Coronavirus disease 2019 (COVID-19).